Karakteristik Pasien Tuberkulosis Paru Pada Masa Pandemi COVID-19 di Poli Paru RSUD dr. H. Chasan Boesoirie - Marwah Widuri Anwar (NHM PRESS, 2022)
Tuberculosis (TB) is still a global health issue and the leading cause of death from infectious diseases. The COVID 19 pandemic has reversed years of standing in TB services. The COVID 19 pandemic has led to an increase in the number of people who are not diagnosed with TB and has become a major source of transmission which has led to high morbidity and mortality rates. The success rate for TB treatment decreased by 69% during the COVID-19 pandemic. This type of research is descriptive research. The population is patients undergoing treatment at the Chasan Boesoirie Hospital polyclinic. The number of samples is 292 patients undergoing tuberculosis treatment at the pulmonary polyclinic from 2020 to 2021. From the results of this study it is hoped that there will be information regarding the development of medical science related to pulmonary tuberculosis. .1%) with the age category of 26-45 years as many as 54 patients (43.5%) with the results of the TCM examination there were 67 patients (54%). Of the total treatment, 95.2% received category 1 treatment with a cure rate of 5.4% and 77.8% of patients with complete treatment.